2022
DOI: 10.3390/ijms231911397
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid Dendritic Cells as a Novel Cell-Based Cancer Immunotherapy

Abstract: Plasmacytoid dendritic cells (pDCs) are multifaceted immune cells with a wide range of innate and adaptive immunological functions. They constitute the first line of defence against multiple viral infections and have also been reported to actively participate in antitumor immune responses. The clinical implication of the presence of pDCs in the tumor microenvironment (TME) is still ambiguous, but it is clear that pDCs possess the ability to modulate tumor-specific T cell responses and direct cytotoxic function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 83 publications
1
12
0
Order By: Relevance
“…43 In addition, our immune infiltration analysis results showed that the expression of CEL was significantly negatively correlated with plasmacytoid dendritic cell, and plasmacytoid dendritic cell were an important link in the initiation of adaptive immune response, participating in the immune inflammatory process of promoting atherosclerosis. 44,45 In our study, CEL expression was downregulated in peripheral blood samples from CAD patients, which means that plasmacytoid dendritic cell will be recruited and activated, and promote the occurrence of atherosclerosis, which also confirms the previous view.…”
supporting
confidence: 90%
“…43 In addition, our immune infiltration analysis results showed that the expression of CEL was significantly negatively correlated with plasmacytoid dendritic cell, and plasmacytoid dendritic cell were an important link in the initiation of adaptive immune response, participating in the immune inflammatory process of promoting atherosclerosis. 44,45 In our study, CEL expression was downregulated in peripheral blood samples from CAD patients, which means that plasmacytoid dendritic cell will be recruited and activated, and promote the occurrence of atherosclerosis, which also confirms the previous view.…”
supporting
confidence: 90%
“…Similarly, cigarette smoke extract-induced NETs also promoted pDCs maturation and activation ( 125 ). The role of pDCs in TME is still ambiguous now ( 126 ). Thus, we hold the opinion that whether NETs-mediated pDCs activation display active immunity functions or involved in immune tolerance is determined by the specific tumor microenvironmental.…”
Section: Nets In Immune Cellsmentioning
confidence: 99%
“…This vaccine consists of a cell line, named "PDC*line", originating from the blood of a patient with plasmacytoid dendritic cell (PDC) leukemia that can be loaded with relevant tumor antigen-derived peptides [8,9]. PDCs are a subtype of DCs playing an essential role in the immune response against viruses through type I interferon secretion [10][11][12]. They also have strong antigen presentation capabilities but have rarely been exploited as a cancer vaccine due to their scarcity [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…PDCs are a subtype of DCs playing an essential role in the immune response against viruses through type I interferon secretion [10][11][12]. They also have strong antigen presentation capabilities but have rarely been exploited as a cancer vaccine due to their scarcity [12][13][14].…”
Section: Introductionmentioning
confidence: 99%